The puffin book of stories for five six-year-olds - Cooling, Wendy; Cox, Steve (Puffin London, 1996)
Suitable for every five-year-olds to share or read aloud, this title includes seventeen stories, full of adventure and magic, by much-loved writers, including Margaret Mahy, Ted Hughes and Malorie Blackman.